INFLUENCE OF GUIDED DISCOVERY METHOD ON MATHEMATICAL COMMUNICATION SKILL OF JUNIOR HIGH SCHOOL STUDENT - Maria Wati Sitorus; Frida Marta Argaretha; Tetty Natalia Sipayung (Universitas Negeri Makassar, 2018)
This study aims to know are (1) the influence of guided discovery method on students' mathematical communication ability; (2) whether students' mathematical communication skills taught by guided discovery methods are higher than those taught by expository methods; (3) the active activities of students taught by guided discovery methods. Sources of data in this study are students of class VII SMPN 1 Patumbak. Class VII-8 as a class of experiments are 30 people and class VII-6 as a control class are 32 people. Based on the analysis of research data, obtained the following results: (1) the results of analysis and regression obtained that the influence of guided discovery method has a positive effect with correlation coefficient 0.831 and coefficient of determination of 69%; (2) the result of t test analysis with tcount = 4.30 and ttable = 1.67 which means tcount> ttable, Ho is rejected which means mathematical communication ability of students who are taught by guided discovery method higher than students taught by method expository; (3) Based on the average level of students' active activity with guided discovery method at each meeting in phase-1 is 13.33%, phase 2 is 22.9%, phase-3 is 15.52%, phase-4 is 16.01%, phase-5 is 7.2%. This shows that with guided discovery method and ideal time tolerance limit the student's active activity is seen and support the mathematics learning process in the set material. So it can be concluded that guided discovery method affects the students' mathematical communication ability